A case report of scar endometriosis with bladder endometriosis - Ramanidevi, T.; Deepika, A.; Sangavi, D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Endometriosis is a common gynaecological condition which occurs in 10-15% women of reproductive age group. It can occur in pelvic and extra pelvic regions like urinary tract, abdominal wall, nervous tract, gastrointestinal tract, nose, lungs, umbilicus and sciatic nerve tract. Previous abdominal wall surgery can lead to scar endometriosis based on implantation theory which is very rare and this is hormone dependent. Here we are presenting a case of recurrent scar endometriosis along with bladder endometriosis which is extremely rare. The common cause for scar endometriosis is caesarean section and hysterotomy. Rarely it can occur following laparoscopy and amniocentesis. The diagnosis is based on the symptoms which are cyclical. USG and MRI can help in the pre-operative diagnosis and FNAC can confirm the diagnosis. Management of scar endometriosis is mainly wide excision of the lesion. Medical management can only be temporary. COCs, progesterone, dienogest and GnRH analogues are the drugs for medical management. Recurrence of scar endometriosis is also rare and association with bladder endometriosis is still rare. Malignant changes are almost less than 1%. This patient had scar endometriosis, bladder endometriosis and adenomyosis, fimbrial endometriosis and ovarian endometrioma. All were excised and post-operative suppression with GnRH was given for 3 months and LNG-IUS was inserted for prevention of recurrence as well as for management of adenomyosis.